Effect of Nusinersen in a late onset spinal muscular atrophy patient for 14 months: A case report. Issue 1 (8th January 2021) - Park, Jin-Mo; Min, Yu-Sun; Park, Donghwi; Park, Jin-Sung
Abstract: Rationale: Spinal muscular atrophy (SMA) is a genetic disorder caused by genetic defect of SMN1 gene. SMA was an untreatable disease until 2016, when Nusinersen an antisense oligonucleotide therapy was approved for treatment. We report the effect of Nusinersen in a late onset SMA for 14 months. Patient concerns: A 13-year-old boy who was diagnosed as SMA with progressive proximal limb weakness was treated with intrathecal injection of Nusinersen. Diagnosis: The patient had progressive proximal limb weakness after 2 years of age. The patient had elevated creatine kinase level and shoed neurogenic changes in the needle electromyography study. After genetic analysis, homozygous deletion in Exon 7 and 8 of SMN1 protein was found and he was diagnosed as late onset SMA. Interventions: Intrathecal Nusinersen was administered per protocol. Outcomes: After 14 months of treatment, the patient showed significant clinical improvement in the revised Hammersmith functional rating scale and 6-minute walk test. Lessons: Although there is limited data on the effect of Nusinersen in late onset SMA patients, our case adds on the effectiveness even in late onset SMA. More studies are needed to consolidate the effects and adverse events of Nusinersen in late onset SMA.